2022
DOI: 10.3390/molecules27041153
|View full text |Cite
|
Sign up to set email alerts
|

Component Analysis and Anti-Colorectal Cancer Mechanism via AKT/mTOR Signalling Pathway of Sanghuangporus vaninii Extracts

Abstract: Sanghuangporus vaninii (Ljub.) L.W. Zhou & Y.C. Dai (SV) is a major cultivar of Sanghuang, which is well known as an excellent anti-tumour drug and reaches the mainstream market in China. Water, 60% ethanol and 95% ethanol were used to extract the drug, and three kinds of polar extracts were obtained separately. Compared with water extracts and 95% ethanol extracts, the 60% ethanol extract had the highest flavonoid content, and its polysaccharide content was greater than that in the 95% ethanol extract and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…S. sanghuang is a widely-used traditional Chinese medicine with an ancient history, and its good antitumor effect has been widely recognized by the international community in recent years ( Han et al, 2016b ; Guo et al, 2022 ). Its antioxidant and anti-inflammatory activities were gradually discovered ( Lin et al, 2017a ); previous studies in our laboratory have also shown that it has a significant therapeutic effect on gout ( Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…S. sanghuang is a widely-used traditional Chinese medicine with an ancient history, and its good antitumor effect has been widely recognized by the international community in recent years ( Han et al, 2016b ; Guo et al, 2022 ). Its antioxidant and anti-inflammatory activities were gradually discovered ( Lin et al, 2017a ); previous studies in our laboratory have also shown that it has a significant therapeutic effect on gout ( Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that huaier extract suppressed cell proliferation and induced apoptosis in HCT116 and HCT8 cells ( Zou et al, 2020 ). Compared with 95% ethanol and water extracts, the 60% ethanol extract of Sanghuangporus vaninii significantly inhibited the AKT/mTOR signaling pathway, as well as induced cell apoptosis and blocked G2/M cell cycle ( Guo S et al, 2022 ). Patrinia scabiosaefolia also regulates the AKT pathway.…”
Section: Application Of Herbs In Crcmentioning
confidence: 99%
“…The description of Sanghuang constituents in ancient literatures is often unclear, and the term has been used to describe products derived from the species Phellinus linteus (homotypic synonyms Inonotus linteus , Tropicoporus linteus ) but more commonly Sanghuang contains species of the genus Sanghuangporus including Sanghuangporus baumii (homotypic synonyms Inonotus baumii , Phellinus baumii ), Sanghuangporus sanghuang (homotypic synonym Inonotus sanghuang ), or Sanghuangporus vaninii (basonym Phellinus vaninii , homotypic synonym Inonotus vaninii ) (Wu & Dai, 2020 ). At present, there are 14 species in the genus Sanghuangporus and of these S. vaninii is the main species applied in the health care and medical field because it produces higher yields, although the research on its pharmacological properties is not thorough (Guo et al., 2022 ; He et al., 2021 ; Wu & Dai, 2020 ). There are a few reports that S. vaninii has the potential to reduce blood lipids (Huang, Huang, et al., 2022 ; Huang, Liu, et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%